IMPROVING STUDENT’S READING COMPREHENSION THROUGH DRTA-STRATEGY AT SMP ST.IGNASIUS MEDAN - Nainggolan, Maria Friska (Jurnal Mutiara Pendidikan Indonesia, 2016)
This study was designed to improve students’ reading comprehension ability through DRTA Strategy. The strategy was selected because it was believed to be able to stimulate or activate the students to be more involved in the reading activities and to facilitate the students to comprehend the texts, especially report texts. The research problem was formulated as follows: “How to apply DRTA strategy in order to improve students reading comprehension at SMP ST.IGNASIUS MEDAN? The study employed a collaborative classroom action research design in which the researcher and the collaborator as researcher team worked together designing the lesson plan, implementing the action, observing the action, and reflecting the action. The subjects of this research were 30 students the first semester students XI of SMP ST.IGNASIUS in the 2013/2014 academic year. The findings of this research study indicated that the DRTA strategy was successful in improving both the students’ ability in comprehending report texts and the students’ involvement in reading activities. Based on the students’ achievement using DRTA strategy in comprehending report texts, it was suggested for the English teachers to apply DRTA strategy as one of many alternatives that can be used in teaching reading skills.